2016
DOI: 10.1088/0953-8984/29/2/025804
|View full text |Cite
|
Sign up to set email alerts
|

Disordered ferromagnetism in Ho2NiMnO6double perovskite

Abstract: Magnetic and dielectric properties of the double perovskite HoNiMnO are reported. The compound is synthesized by nitrate route and is found to crystallize in monoclinic P2/n space group. Lattice parameters obtained by refining powder x-ray diffraction data are; a  =  5.218(2) Å, b  =  5.543(2) Å, c  =  7.480(3) Å and the monoclinic angle is [Formula: see text](4). A phase transition is observed at [Formula: see text] K in the temperature-dependent magnetization curve, M(T). The inverse magnetic susceptibility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 38 publications
7
29
0
Order By: Relevance
“…The new established interactions lead to a canted antiferromagnetic arrangement of Dy 3+ magnetic moments with respect to the Ni 2+ and Mn 4+ ferromagnetic-sublattices. A similar behaviour was recently observed in other R2NiMnO6 double perovskites 32,33 . This may explain the relatively low magnetic moment of Dy2NiMnO6 even under high magnetic fields as found at low temperatures.…”
Section: Resultssupporting
confidence: 89%
“…The new established interactions lead to a canted antiferromagnetic arrangement of Dy 3+ magnetic moments with respect to the Ni 2+ and Mn 4+ ferromagnetic-sublattices. A similar behaviour was recently observed in other R2NiMnO6 double perovskites 32,33 . This may explain the relatively low magnetic moment of Dy2NiMnO6 even under high magnetic fields as found at low temperatures.…”
Section: Resultssupporting
confidence: 89%
“…All the systems therefore are in pure phase according to X-ray diffraction results. The refined patterns are reported or will be published elsewhere [14,15,16,17].…”
Section: Resultsmentioning
confidence: 99%
“…Double perovskite oxides (A 2 NiMnO 6 , A = rare earth) have drawn great attention owning to the unique physical property and potential applications, including sensors, spintronics, large magnetocapacitance and magnetoresistance devices. Among them, La 2 NiMnO 6 is an attractive material with large magneto‐capacitance, magnetoresistance effect and super high ferromagnetic (FM) transition temperature T C1 ≈ 280 K .…”
Section: Introductionmentioning
confidence: 99%
“…The biphasic nature (Pbnm and R‐3c) exists in all the samples and the R‐3c phase displays the increasing trend with the increase of Cu content . Apart from the La 2 NiMnO 6 , researchers also focus on the investigation of other A 2 NiMnO 6 oxides simultaneously . For example, Jia et al reported the multiple magnetic phase transitions and magnetocaloric effect in A 2 NiMnO 6 ( A = Dy, Ho, and Er), including three magnetic phase transitions ( T R , T d–f , T C ) were observed for R 2 NiMnO 6 compounds corresponding to the rare earth ordering, 3d–4f exchange, and 3d metal ordering, respectively .…”
Section: Introductionmentioning
confidence: 99%